Answer:
Explanation:
Ok so for question one we use the Pythagorean theorem, which is a^2+b^2=c^2
a is the shortest leg, b is the leg that is not the hypotenuse. and c is the hypotenuse which is the opposite leg to the right angle.
Question 1: a=9,b=12,c=x
(9)^2+(12)^2=(x)^2
81+144=(x)^2
225=(x)^2
x=15
Question 2: a=10,b=24,c=x
(10)^2+(24)^2=(x)^2
100+576=(x)^2
676=(x)^2
x=26
Question 3: a=3,b=7,c=x
(3)^2+(7)^2=(x)^2
9+49=(x)^2
58=(x)^2
x=root58, or 7.615773
Question 4: a=6,b=x, c=10
(6)^2+(x)^2=(10)^2
36+(x)^2=100
Subtract 36 from both sides
(x)^2=64
x=8
Question 5: a=6,b=x, c=24
(6)^2+(x)^2=(24)^2
36+(x)^2=576
Subtract 36 from both sides
(x)^2=540
x=6root15, or 23.2379
Question 6: a=1, b=1, c=x
(1)^2+(1)^2=(x)^2
1+1=(x)^2
2=(x)^2
x=root2, or 1.414213562
Question 7: a=8, b=x, c=21
(8)^2+(x)^2=(21)^2
64+(x)^2=441
Subtract 64 from both sides
(x)^2=377
x=root377, or 19.41648784
Question 8: a=24, b=x, c=30
(24)^2+(x)^2=(30)^2
576+(x)^2=900
Subtract 576 from both sides
(x)^2=324
x=18
Question 9: a=5,b=9, c=x
(5)^2+(9)^2=(x)^2
25+81=(x)^2
106=(x)^2
x=root106, or 10.29563014
Question 9 Part B: a=3, b=5, c=y
(3)^2+(5)^2=(y)^2
9+25=(y)^2
34=(y)^2
root34, or 5.830951895=y